Sea bass (Lateolabrax maculatus) exerts anti‐ulcerative colitis effects through gut microbiota modulation - Jiali Chen; Yuhang Xiao; Kejian Wang; Xiuqiong Fu; Yueyao Fan; Muhammad Jahangir Hossen; Yingjie Chen; Weibin Bai; Zhiling Yu; Baojun Xu (Food Frontiers, 2024)
Abstract Traditional Chinese medicinal books have noted that sea bass (Lateolabrax maculatus) may effectively manage inflammation‐linked conditions. The folk use of sea bass during pregnancy as nutritional care is also popular in China. However, scientific verification of health benefits of sea bass remains a lack of report. Our previous studies have proven that sea bass has therapeutic benefits for ulcerative colitis (UC). However, a further investigation on the interacted mechanism among sea bass, UC, and gut microbiota has still not been fully explored and clarified. Hence, gut microbiota as the crucial mechanism of UC was evaluated. Gut ecosystem was analyzed by 16sRNA sequencing. The potential microbial biomarker was found through LEfSe analysis. Flow cytometry was then further applied to verify the identified biomarker. Results revealed that sea bass could effectively recover the abundance of UC‐mediated microbiota. LEfSe analysis found that Christensenellaceae could be identified as the potential biomarker for sea bass‐mediated gut microbiota in UC. Further in vitro study conjointly confirmed that the identified bioactive constituent of sea bass could significantly promote the growth of Christensenella minuta. Sufficient results derived that sea bass could ameliorate UC through gut microbiota modulation. C. minuta was identified as the promising microbial biomarker for the mechanism of sea bass in treating intestinal inflammation. It provided further elucidation on the pharmacological mechanism of sea bass in alleviating UC through gut microbiota modulation. It is a crucial driving force for the progress of scientific research on the dietary therapy of sea bass.